Les expulsés allemands. Des victimes en quête de reconnaissance - Florence Lelait (Amnis)
The debate on West Germany national-socialist past is recurrent since 1945. Lately, it has reached a turning point essentially because of some scientific and literary publications. The country discovers again that it was not only the country of the executioners, but also a country of victims. Among them, there were particularly billion of people, who got expelled both from the Eastern German territories, and Eastern and Central Europe. The country largely recognized the victime status of this population on a legislative and political level. But those people bid higher, considering that expulsion was a crime against humanity, in order to put forward territorial revendications, which are less and less acceptable. This image of victim and suffering has been nourished in different ways on the cultural level. And they enventually used their compatriots’compassion regarding the expellees from Yougoslavia and Kosovo, to re-gain favour in public opinion. However this phenomenon is limited, as it could be seen through the confrontation of two exhibitions in Berlin, which both represented two different conceptions of history.